THE UNITED NATIONS COUNCIL’S INTERVENTION IN THE RECONCILIATIAON OF HUMAN RIGHTS AND FUNDAMENTAL FREEDOMS IN NORTH KOREA - Imam Budiman; Muhandis Rajab; Haya Abiyyu; Diani Nurul Yanti; Iqbal Nanda (Jurnal Info Sains : Informatika dan Sains, 2023)
Human rights are the basic rights given to mankind by God. They are universal and must be protected, respected and maintained. No one should ignore, reduce or deprive them. Therefore, the implementation of violations of human rights principles is the responsibility of the state as well as the responsibility of mortgage. The United Nations has incorporated respect and appreciation of human rights into the "United Nations Charter" in its charter, which was unanimously adopted by the UN General Assembly on December 10, 1948. But the charter seemed to be ignored by North Korea. North Korea has one of the worst human rights records. The North Korean government has violated human rights in the form of crimes against humanity against civilians. North Korea’s violations of human rights should be the responsibility of the country concerned, as well as the common responsibility of the international community. Therefore, in this case, the United Nations has acted as a protection shield against civilians, preventing criminals from taking actions to treat civilians casually. This Journal answers the question of why foreign aid and the United Nations cannot solve North Korea’s human rights violations. Researchers are concerned about North Korea’s isolationist political conditions and the attitude of the ruling government, which are the reasons why foreign aid has failed to address human rights violations. The results of this study show that because the North Korean government is very isolated and dominant in providing and distributing foreign aid, foreign aid cannot solve North Korea’s human rights violations